Terms of trade : glossary of international economics - Deardorff, Alan V. (World Scientific, 2014)
This book is a glossary of terms in international economics, covering both international trade and international finance with emphasis on economic issues. The content includes an expanded glossary, a picture gallery of diagrams illustrating key concepts, over 30 subject-categorized lists of terms, and a section on the origins of certain important terms.